Use of polymerase chain reaction in the diagnosis of acute bacterial meningitis in children - Nacro, Boubacar; Konate, Souleymane; Gaudreault, Suzanne; Sangare, Lassana (Journal of Pediatric Infectious Diseases, 2008)
To improve the epidemiologic surveillance of bacterial meningitis in Burkina Faso, cerebrospinal fluid samples from suspected acute bacterial meningitis in the Department of Pediatrics at Centre Hospitalier Universitaire Souro Sanou (CHU-SS), Bobo Dioulasso were tested by polymerase chain reaction (PCR) assay and results were compared to standard bacteriologic methods. The study was conducted over 13 months (March 2002 until March 2003) and included 170 suspected cases of meningitis in which lumbar punctures were performed. Cerebrospinal fluid samples were cultured on selective media and bacterial isolates were identified in 60 cases as follows; 56% Neisseria meningitidis, 22% Streptococcus pneumoniae, and 22% Haemophilus influenzae type b. Etiologic agents were detected by PCR in 77 cases as follows; 53% N. meningitidis, 21% S. pneumoniae, and 26% H. influenzae type b. Of the 162 samples evaluated by Gram stain, 64 (39.5%) were positive compared to 77 (45.5%) of the same samples that tested positive by PCR. Of the 88 samples selected for bacterial culture, 60 (68.2%) or 37% of the 162 total samples were positive. In the latex agglutination performed on 83 samples, 74 (89.2%), or 45.7% of the 162 total were positive. Sensitivity, specificity, positive predictive value, and negative predictive value of PCR measured against the results of standard cultures of Streptococcus were 76.92%, 97.3%, 83.33% and 96% respectively; for H. influenzae typeb, values were 84.6%, 89.18%, 57.89% and 97.05%, respectively and for N. meningitidis, values were 100%, 86.8%, 82.92%, and 100%, respectively. These results suggest that PCR is a useful technique for the evaluation of bacterial meningitis, when used in conjunction with bacterial cultures.
Keywords: Acute bacterial meningitis; Burkina Faso; child; PCR